2000
DOI: 10.1038/sj.sc.3101005
|View full text |Cite
|
Sign up to set email alerts
|

Forced oscillation technique to detect and monitor tracheal stenosis in a tetraplegic patient

Abstract: Study design: A case report. Objectives: To demonstrate forced oscillation technique's (FOT) utility in a tetraplegic patient with tracheostenosis. Setting: A Rehabilitation Hospital, BrasõÂ lia, Brazil. Methods: Serial evaluations of spirometry, bronchoscopy and forced oscillation assessment. Results: A 16-year-old male with C7 spinal cord injury, initially required mechanical ventilation and subsequent tracheostomy over a period of 4 weeks. Five months after the accident the onset of tracheostenosis was diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…This capability was demonstrated in our index case reported earlier. 6 The relationship of respiratory resistance to tracheal stenotic diameter is most marked at low frequencies. As frequency rises, the measured resistance falls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This capability was demonstrated in our index case reported earlier. 6 The relationship of respiratory resistance to tracheal stenotic diameter is most marked at low frequencies. As frequency rises, the measured resistance falls.…”
Section: Discussionmentioning
confidence: 99%
“…Our present study of the usefulness of forced oscillation technique (FOT) in tracheostenosis was suggested by our experience with a previously reported patient. 6 Other authors have suggested another technique performed at quiet breathing during bronchoscopy for preoperative assessment of tracheal stenotic lesions. 7 Our objective was to assess FOT as a potential screening and follow-up method, with a view to reducing the dangers of stenotic tracheal lesions at the time of diagnosis, while reducing the need for costly invasive and radiologic exams.…”
mentioning
confidence: 99%
“…Changes in central airway calibre correlate more strongly with resistive parameters and are less well represented in the inertive spectral range. Finally, it should be noted that oscillometric reactance occasionally demonstrates a low-to-mid frequency plateau in the Xrs (f) tracing, which is suggestive of possible upper airway obstruction [47][48][49][50].…”
Section: Respiratory Reactancementioning
confidence: 98%
“…IOS has been applied in a number of clinical situations including detection of fixed airway obstruction, upper airway resistance in obstructive sleep apnea, tracheal stenosis, and significant inhalational exposures. 1719 …”
Section: Introductionmentioning
confidence: 99%